2014
DOI: 10.4161/mabs.28282
|View full text |Cite
|
Sign up to set email alerts
|

Ocaratuzumab, an Fc-engineered antibody demonstrates enhanced antibody-dependent cell-mediated cytotoxicity in chronic lymphocytic leukemia

Abstract: (2014) Ocaratuzumab, an Fc-engineered antibody demonstrates enhanced antibody-dependent cellmediated cytotoxicity in chronic lymphocytic leukemia, mAbs, 6:3, 748-754,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…ADCC assays have been previously used as a surrogate measure of the cellular cytotoxicity of CD20 mAbs (20,23,43). Our data showed that NK cell ADCC did not predict ADCP capacity, a conclusion compatible with published data stating that the distance of mAb binding epitopes from the cell membrane differentially affects the ability to activate ADCC (more proximal) or ADCP (more distal; ref.…”
Section: Discussionsupporting
confidence: 88%
“…ADCC assays have been previously used as a surrogate measure of the cellular cytotoxicity of CD20 mAbs (20,23,43). Our data showed that NK cell ADCC did not predict ADCP capacity, a conclusion compatible with published data stating that the distance of mAb binding epitopes from the cell membrane differentially affects the ability to activate ADCC (more proximal) or ADCP (more distal; ref.…”
Section: Discussionsupporting
confidence: 88%
“…For example, compared with rituximab, ofatumumab exhibits increased CDC by binding to a different CD20 epitope [24]. Fc alterations are illustrated by ocaratuzumab (AME-133v), which exhibits increased ADCC via an amino acid substitution in the Fc domain that alters Fcc receptor (FccR) interaction [27].…”
Section: Introductionmentioning
confidence: 99%
“…It was optimized through protein engineering for increased CD20 affinity and greater ability to mediate ADCC [77]. In preclinical studies, ocaratuzumab is~20 times more effective at mediating ADCC at very low concentrations that may facilitate sub-cutaneous dosing [78]. This antibody induces higher NK cell-mediated ADCC over rituximab and ofatumumab and in a similar way to obinutuzumab.…”
Section: Scientific Rationalementioning
confidence: 97%